Klarowność wypowiedzi dramatycznej, czyli irlandzki dramat końca wieku dwudziestego - Grene, Nicholas (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
Synge, with his “fully-flavoured” Hiberno-English established a tradition of Irish theatrical eloquence that has come down into the contemporary period in the lyrical fluencies of Brian Friel, the vatic speech of Frank McGuinness and the Midlands poeticism of Marina Carr. Tom Murphy, however, set a different sort of precedent, resistant to such eloquence, forging a stage speech instead from the broken language of the inarticulate. The aim of this paper is to explore the rejection of ‘poetry talk’ in contemporary Irish drama, and the various ideolects created by Billy Roche, Conor McPherson, Martin Mc- Donagh, Mark O’Rowe and Enda Walsh.